POLA PENDIDIKAN PESANTREN MUHAMMADIYAH : STUDI KURIKULUM PONDOK PESANTREN MODERN DARUL ARQOM PATEAN KENDAL - KIRNO KIRNO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research is a field research using descriptive method and qualitative approach. The curriculum pattern at the Darul Arqom Patean Kendal Modern Islamic Boarding School integrates the curriculum of the Ministry of Religion and the Ministry of National Education where the subjects are a combination of the Ministry of Religion and the Ministry of National Education, LP2M and boarding schools with an emphasis on group integration ad-Dirasah al-Islamiyah, ad-Dirasah al-Lughowiyah, ad- Dirasah al-'Ammah. The curriculum is known as Kulliyatul Mu'allimin Al-Islamiyah (KMI) which has the goal of producing teachers/ustadz who are able to practice what they have learned in Islamic boarding schools. The distinctive feature of the curriculum developed in the KMI program is the existence of a compulsory service program. Santri live in disciplined huts for 24 hours straight, with the guidance of teachers and Kyai which is carried out through Intra-curricular, Co-Curricular and Extra-Curricular programs. The implementation of the curriculum at the Modern Darul Arqom Patean Kendal Islamic Boarding School is carried out first by planning by organizing an educational program using a package system, where all learning programs and learning loads have been determined for each class in accordance with the curriculum structure that applies to each education unit with various student activities starting from morning to night, this planning is carried out by the stake holders of the pesantren every new school year and the results of the planning are documented in the KMI document, second, the process of implementing the students adjusts the teaching and learning hours, after the KBM hours are finished the pesantren activities run as they should lead to the KMI curriculum philosophy which emphasizes on the importance of varied methods, professional and role model teachers, and lessons at KMI are 100% religion and 100% general. making the educational process will be focused on the expected goals, the three evaluations are carried out before the end of the school year with an evaluation component, namely evaluation of the teacher or asatid and assessment of student learning outcomes, the form of assessment is carried out through test and non-test assessments. ABSTRAKPenelitian ini adalah penelitian lapangan dengan menggunakan metode deskriptif dan pendekatan kualitatif. Pola kurikulum di Pondok Pesantren Modern Darul Arqom Patean Kendal mengintegrasikan mengintegrasikan kurikulum pondok Kemenag dan Kemendiknas dimana mata pelajaran merupakan gabungan Kemenag dan Kemendiknas, LP2M dan kepondokan dengan menekankan pada keterpaduan kelompok ad-Dirasah al-Islamiyah, ad-Dirasah al-Lughowiyah, ad-Dirasah al-‘Ammah. Kurikulum dikenal dengan Kulliyatul Mu’allimin Al-Islamiyah (KMI) yagn mempunyai tujuan yaitu mencetak guru/ustadz yang mampu mengamalkan apa yang telah mereka dapat di pesantren. Ciri khas kurikum yang dikembangkan dalam program KMI adalah adanya program wajib pengabdian. Santri hidup di dalam pondok yang berdisiplin selama 24 jam penuh, dengan bimbingan para guru dan Kyai yagn dilakukan melalui program Intra-kurikuler, Ko-Kurikuler dam Ekstra Kurikuler. Pelaksanaan kurikulum di Pondok Pesantren Modern Darul Arqom Patean Kendal dilakukan pertama perencanaan dengan menyelenggarakan program pendidikan dengan menggunakan sistem paket, dimana seluruh program pembelajaran dan beban belajar yang telah ditentukan untuk setiap kelas sesuai dengan struktur kurikulum yang berlaku pada tiap satuan pendidikan degam berbagai kegiatan santri mulai pagi sampai malam, perencanaan ini dilakukan oleh stake holder pondok setiap tahun ajaran baru dan hasil perencanaan tersebut didokumentasikan aturannya dalam dokumen KMI, kedua, proses pelaksanaan santri menyesuaikan jam KBM, setelah jam KBM selesai kegiatan pesantren berjalan sebagaimana mestinya mengarah pada falsafah kurikum KMI yang menekankan pada pentingnya metode yagn variatif, guru profesional dan jadi teladan, dan pelajaran di KMI aalah agama 100% dan umum 100%. menjadikan proses pendidikan akan tertuju pada tujuan yang diharapkan, ketiga evaluasi dilakukan sebelum akhir tahun pelajaran dengan komponen evaluasi yaitu evaluasi terhadap guru atau asatid dan penilaian hasil belajar santri, bentuk penailaian dilakukan melalui penilaian tes dan non tes.